1990
DOI: 10.1136/thx.45.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of thin section computed tomography with bronchography for identifying bronchiectatic segments in patients with chronic sputum production.

Abstract: Computed tomography is widely used in the investigation of patients in whom bronchiectasis is suspected, despite considerable variation in its reported sensitivity and specificity. The findings with 3 mm high resolution computed tomography were compared at segmental level with bronchography by two radiologists independently in 27 patients (aged 20-67 years) undergoing investigation of chronic sputum production. Fifteen patients were found to have bronchiectasis by both investigations. Five were identified by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 12 publications
(1 reference statement)
0
19
0
Order By: Relevance
“…The schoolchildren scored in the present study had normal lung function both at visits 1 and 2. In schoolchildren, bronchiectasis became an important morphological change and HRCT of the chest is considered the gold standard for diagnosing bronchiectasis [23]. This might, in part, explain why in the present study chest radiograph scores in schoolchildren showed less progression over the 3-yr period than the scores in preschool children.…”
Section: Discussionmentioning
confidence: 53%
“…The schoolchildren scored in the present study had normal lung function both at visits 1 and 2. In schoolchildren, bronchiectasis became an important morphological change and HRCT of the chest is considered the gold standard for diagnosing bronchiectasis [23]. This might, in part, explain why in the present study chest radiograph scores in schoolchildren showed less progression over the 3-yr period than the scores in preschool children.…”
Section: Discussionmentioning
confidence: 53%
“…The sensitivity rate in these studies has ranged from 60-100%, while specificity has been of the order of 90-100% [7][8][9][10][11][12][13]. However, there has not yet been a systematic study to evaluate CT of the thorax in comparison to bronchography for demonstration of CB in ABPA.…”
Section: Discussionmentioning
confidence: 99%
“…However, there has not yet been a systematic study to evaluate CT of the thorax in comparison to bronchography for demonstration of CB in ABPA. In studies of CT of thorax with the standard 10 mm sections at 10 mm intervals for demonstration of bronchiectasis, it was felt that the bronchi were not sharply visualized, due to partial volume averaging effect [7,8,11,13]. Furthermore, a gap of 10 mm between the sections may lead to small bronchiectatic lesions being missed [8,9,11], especially in bronchi that course horizontally as their axes lie parallel to the transverse plane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 There have been many computerized tomography (CT) scoring systems that evaluate the radiologic severity of bronchiectasis, although most of these were developed to evaluate the severity of cystic fibrosis (CF). 4 Many previous studies showed that the radiologic CT score was more sensitive in predicting disease progression than pulmonary function test (PFT) parameters in CF.…”
Section: Introductionmentioning
confidence: 99%